Detecting Ethambutol Resistance in Mycobacterium tuberculosis Isolates in China: A Comparison Between Phenotypic Drug Susceptibility Testing Methods and DNA Sequencing of embAB - Li, Ma-chao; Chen, Rong; Lin, Shi-qiang; Lu, Yao; Liu, Hai-can; Li, Gui-lian; Liu, Zhi-guang; Zhao, Xiu-qin; Zhao, Li-li; Wan, Kang-Lin (Frontiers in Microbiology, 2020)
With the increasing incidence of drug-resistant tuberculosis (TB), determining a rapid and accurate drug susceptibility testing (DST) method to identify ethambutol (EMB) resistance in Mycobacterium tuberculosis (M. tuberculosis) has become essential for patient management in China. Herein we evaluated the correlation between three phenotypic DST methods, namely proportion method (PM), MGIT 960 system, and microplate alamar blue assay (MABA), and DNA sequencing of embAB in 118 M. tuberculosis isolates from China. When the results of the phenotypic DST methods were compared with those of DNA sequencing, the overall agreement and kappa values of PM, MGIT 960 system, and MABA were 81.4% and 0.61, 77.1% and 0.55, and 84.7% and 0.67, respectively. The agreement for EMB resistance between MABA and PM was significantly higher than that between MGIT 960 system and PM (P=0.02). Moreover, among the isolates with detectable embAB mutations, 97.3% (72/74 isolates) harbored mutations in embB. The analysis of embB mutations predicted EMB resistance with 81.3% sensitivity, 86.8% specificity, and 83.1% accuracy. Thus, MABA may be a better phenotypic DST method for detecting EMB resistance. DNA sequencing of embB may be useful for the early identification of EMB resistance and the consequent optimization of the treatment regimen.